Wiley 2012 interpretation and application of International Financial Reporting Standards - Mackenzie, Bruce; Coestee, Danie; Njikizana, Tapira; Chamboko, Raymond (Hoboken, New Jersey John Wiley & Sons, 2012)
For many years, the International Accounting Standards Board (IASB) has been working to develop a set of accounting standards that can be used to bring about uniformity in financial reporting around the world.
1. Introduction to International Financial Reporting Standards -- 2. Conceptual Framework -- 3. Presentation of Financial Statements -- 4. Statement of Financial Position -- 5. Statement of Profit or Loss and Other Comprehensive Income, and Changes in Equity -- 6. Statement of Cash Flows -- 7. Accounting Policies, Changes in Accounting Estimates, and Errors -- 8. Inventory -- 9. Property, Plant, and Equipment 147 10 Borrowing Costs -- 11. Intangible Assets 205 12 Investment Property -- 13. Interests in Associates -- 14. Interests in Joint Ventures -- 15. Business Combinations and Consolidated Financial Statements -- 16. Shareholders' Equity -- 17. Share-Based Payment -- 18. Current Liabilities, Provisions, Contingencies, and Events After the Reporting Period -- 19. Employee Benefits -- 20. Revenue Recognition, Including Construction Contracts -- 21. Government Grants -- 22. Leases -- 23. Foreign Currency -- 24. Financial Instruments -- 25. Fair Value -- 26. Income Taxes -- 27. Earnings Per Share -- 28. Operating Segments -- 29. Related-Party Disclosures -- 30. Accounting and Reporting by Retirement Benefit Plans -- 31. Agriculture -- 32. Extractive Industries -- 33. Accounting for Insurance Contracts -- 34. Interim Financial Reporting -- 35. Inflation and Hyperinflation -- 36. First-Time Adoption of International Financial Reporting Standards.
Includes index.
Includes summary of key provisions of US GAAP vs. IFRS.
Keywords: Accounting -- Standards; International business enterprises -- Accounting